2016
DOI: 10.1007/s12529-016-9550-2
|View full text |Cite
|
Sign up to set email alerts
|

Upswings in Cheerful Mood and Disease Activity in Patients with Rheumatoid Arthritis

Abstract: The findings suggest interesting possibilities for the diagnosis and monitoring of disease activity in rheumatoid arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In a recent study, López-Benítez et al (in press) have found that, compared to low trait cheerfulness people, individuals characterized by high trait cheerfulness experienced a larger affective state change as a consequence of watching amusing and sad stimuli. The authors interpreted this finding as larger affective sensitivity or permeability to the environment, thus promoting some psychological, social, and physical benefits in high trait cheerfulness individuals (e.g., Yip and Martin, 2006; Carretero-Dios et al, 2014; Delgado-Domínguez et al, 2016). In this sense, it is possible that the presentation of a cue to anticipate the task might be a powerful element to capture and focus high cheerfulness people’s attention, promoting a better permeability (larger preparation effects) to it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, López-Benítez et al (in press) have found that, compared to low trait cheerfulness people, individuals characterized by high trait cheerfulness experienced a larger affective state change as a consequence of watching amusing and sad stimuli. The authors interpreted this finding as larger affective sensitivity or permeability to the environment, thus promoting some psychological, social, and physical benefits in high trait cheerfulness individuals (e.g., Yip and Martin, 2006; Carretero-Dios et al, 2014; Delgado-Domínguez et al, 2016). In this sense, it is possible that the presentation of a cue to anticipate the task might be a powerful element to capture and focus high cheerfulness people’s attention, promoting a better permeability (larger preparation effects) to it.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, it has been pointed out that cheerfulness affects dispositions of the exhilaration response (Ruch, 1997), predicts most of sense-of-humor facets, contributes to the use of humor as a recovery strategy, and is associated with affiliative and self-enhancing humor styles (Ruch and Hofmann, 2012). Moreover, other research support the applicability and relevance of cheerfulness in areas as diverse as personality, health, or emotion (e.g., Ruch et al, 1996, 1997; Yip and Martin, 2006; Ruch and Köhler, 2007; Papousek and Schulter, 2010; Carretero-Dios et al, 2011; Ruch and Hofmann, 2012; Delgado-Domínguez et al, 2016). …”
Section: Introductionmentioning
confidence: 97%
“…Recently, the state-trait cheerfulness influence on self-reported disease activity levels in rheumatoid arthritis patients (Delgado-Domínguez et al, 2016 ) was investigated in a cross-sectional study. State cheerfulness and trait cheerfulness were assessed at the same time as a blood sample was taken from patients in order to analyze the corresponding biochemical parameters (Erythrocyte sedimentation rate and C-reactive protein), and just before measuring patient-reported disease activity.…”
Section: Validationmentioning
confidence: 99%
“…Moreover, higher state cheerfulness was associated with lower values of C-reactive protein. Finally, results showed that the relationship between the biochemical parameters of rheumatoid arthritis and patient-reported disease activity partially depended (i.e., mediation analysis) on cheerful mood at the moment of assessment (Delgado-Domínguez et al, 2016 ).…”
Section: Validationmentioning
confidence: 99%
“…They may help to provide a momentary respite from ongoing stress and adversity 13 , and may perturb downward spirals of chronic negative moods and stress perhaps even in emotion-related psychopathology 4 . Some research reported that positive emotional experiences such as short-lived joy or amusement may exert transient analgesic-like effects 58 . However, even when exposed to the same amount of positive emotion elicitors in their daily lives, some people benefit more than others.…”
Section: Introductionmentioning
confidence: 99%